Medicine shortages-risks and solutions - Miljković, Nenad (Archives of Pharmacy, 2022)
Medicine shortages result in great risk for the continuity of patient care especially for antimicrobial treatment, potentially enhancing resistance rates and having a higher economic impact (1-2). This study aims to identify, describe, assess, and assign risk priority levels to potential failures following substitution of antimicrobial treatment due to shortages among European hospitals. Health-care failure mode and effect analysis was applied to six hospitals in Austria, Belgium, Croatia, Greece, Spain, and Serbia in 2018 and 2019. Multidisciplinary teams identified processes, failure modes, causes, and corrective actions related to antibiotic substitution following medicine shortages. Severity, probability, and hazard scores (HSs) of failure modes/causes were analyzed using IBM SPSS Statistics®. Through HFMEA, 74 failure modes were identified, with 53 of these scoring 8 or above on the basis of assigned severity and probability for a failure due to data scarcity on availability of antibiotics and non-supportive IT systems. Severity of failure modes differed before and after corrective actions in hospitals in Croatia, Greece and Serbia (p < 0.005). Their probability differed in all study hospitals (p < 0.005) when compared before and after implemented corrective actions. The highest number of failure-mode causes was detected in a hospital in Croatia (46) and the lowest in a hospital in Spain (16). Proposed corrective actions can address failure modes and lower HSs; therein, all teams proposed the following: structuring communication among stakeholders, introducing electronic prescribing, and increasing effectiveness of the ward stock assessment. These proposed actions led to HS reductions up to 83%.